Sesquiterpene Lactones Attenuate Paclitaxel Resistance Via Inhibiting MALAT1/STAT3/ FUT4 Axis and P-Glycoprotein Transporters in Lung Cancer Cells - Ding, Yaming; Zhen, Zhang; Nisar, Muhammad Azhar; Ali, Farman; Din, Riaz Ud; Khan, Muhammad; Mughal, Tafail Akbar; Alam, Gulzar; Liu, Linlin; Saleem, Muhammad Zubair (Frontiers in Pharmacology, 2022)
Paclitaxel resistance is a challenging factor in chemotherapy resulting in poor prognosis and cancer recurrence. Signal transducer and activator of transcription factor 3 (STAT3), a key transcription factor, performs a critical role in cancer development, cell survival and chemoresistance, while its inactivation overwhelms drug resistance in numerous cancer types including lung cancer. Additionally, the fucosyltransferase 4 (FUT4) is a crucial enzyme in post-translational modification of cell-surface proteins involved in various pathological conditions such as tumor multidrug resistance (MDR). The P-glycoprotein (P-GP) is the well-known ABC transporter member that imparts drug resistance in different cancer types, most notably paclitaxel resistance in lung cancer cells. LncRNA-MALAT1 exerts a functional role in the cancer development as well as the drug resistance and is linked with STAT3 activation and activity of FUT4. Moreover, STAT3-mediated induction of P-GP is well-documented. Natural compounds of Sesquiterpene Lactone (SL) family are well-known for their anticancer properties with particular emphasis over STAT3 inhibitory capabilities. In this study, we explored the positive correlation of MALAT1 with STAT3 and FUT4 activity in paclitaxel resistant A549 (A549/T) lung cancer cells. Additionally, we investigated the anticancer activity of two well-known members of SLs, alantolactone (ALT) and Brevilin A (Brv-A), in A549/T lung cancer cells. ALT and Brv-A induced apoptosis in A549/T cells. Furthermore, these two natural SLs suppressed MALAT1 expression, STAT3 activation, and FUT4 and P-GP expression which are the hallmarks for paclitaxel resistance in A549 lung cancer cells. The inhibition of MALAT1 enhanced the competence of these SLs members significantly, which accounted for the growth inhibition as well as anti-migratory and anti-invasive effects of ALT and Brv-A. These findings suggest SLs to be the promising agents for overcoming paclitaxel resistance in A549 lung cancer cells.